(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This study makes an effort to delve into the significance of human values in today’s interconnected world. Without human values, human civilization may not be able to maintain itself. Consequently, we must have this conversation in order to raise contemporary society’s consciousness of human values. Everybody can see that modern civilization is in the midst of a lot of problems. The contemporary world is well-known to be experiencing a human value crisis. It is thought that by putting human values into practice in every culture, a number of national and international issues might be resolved. In order to achieve this, human dignity must be held in the greatest esteem by all members of human society. When it comes to society, human values are paramount. Priority is given to human ideals rather than societal values. A person’s view of humanity as a whole is what gives them worth. While it’s true that people are society’s primary focus, it’s also true that contemporary society can never really disappear so long as people are a part of it. Because of how much better communication is now because to technology, our words, deeds, and thoughts directly impact a wider audience than in the past. By writing this piece, the author hopes to get a better grasp of human values’ societal relevance and the role they’ve played in shaping modern civilization.